Structure and tectonics of 85°E Ridge from analysis of Geopotential data - Anand, S.P.; Rajaram, M.; Majumdar, T.J.; Bhattacharyya, R. (My University, 2009)
The Bay of Bengal (BOB) sedimentary basin is one of the largest offshore sedimentary basins of the world having the thickest accumulation of sediments which mask the underlying crust and it is the Geopotential data that offers the unique opportunity of seeing below the thick sediments. Satellite derived Free Air Gravity (FAG) data, marine magnetic data, bathymetry, available seismic profiles and isopach maps over the Bay of Bengal are utilized in the present paper to throw light on the nature and tectonics of the BOB with particular emphasis on the 85°E Ridge. Combined analysis of gravity and magnetic data along six EW profiles of length varying from 325 to 440 km is undertaken, incorporating seafloor spreading anomalies in the model. Of the several theories put forth for the evolution of the 85°E Ridge, the present study supports the sagging of the crust and rules out the hotspot trace and magmatic under-plating theories. The crustal model derived from the magnetic profile analysis suggests that the 85°E Ridge does not extend to the North of 15°N latitude and this is supported by the Euler solutions of the FAG and the long wavelength filtered FAG. However, the intermediate wavelength filtered FAG suggests that the 85°E Ridge extends up to the Ocean Continent Boundary thereby suggesting that the 85°E Ridge thins out dramatically to the North of 15°N latitude. Analysis of gravity data along 17°N latitude profile predicts that in the northern segment the 85°E Ridge is a geo-morphological feature within the sediments above the basement whereas to the South of 15°N latitude it is a feature within the oceanic crust (below the basement). Further the reverse magnetization associated with the seafloor spreading anomalies lying on the 85°E Ridge belongs either to the Albian period or the anomaly A34/A33. The 85°E Ridge would be younger than these seafloor spreading anomalies and would have formed due to horizontal compressional forces of the lithosphere preceding development of the subduction zone at the Andaman trench.
Keywords: Bay of Bengal; Geopotential data; Seafloor spreading anomalies; 85°E Ridge